2009
DOI: 10.1080/15368370902724633
|View full text |Cite
|
Sign up to set email alerts
|

Oncothermia Treatment of Cancer: From the Laboratory to Clinic

Abstract: Oncothermia is a long-time applied method (since 1989) in oncology. Its clinical results excellently show its advantages, however the details of its mechanism are under investigation even today. The method is based on a self-selective process of energy concentration and targets the membrane of the malignant cell, using the temperature gradient and the beta-dispersion of the membrane proteins. To prove the theory we show the experimental evidences in vitro experiments where we showed the definite difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 24 publications
1
74
0
Order By: Relevance
“…Previous studies have shown that high temperatures can damage and kill cancer cells, usually with minimal injury to normal tissues. mEHT which is also described as 'oncothermia' in Europe is a personalized treatment using energy delivery to the targeted tumor (9). This treatment concentrates the absorbed energy to intercellular electrolytes (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that high temperatures can damage and kill cancer cells, usually with minimal injury to normal tissues. mEHT which is also described as 'oncothermia' in Europe is a personalized treatment using energy delivery to the targeted tumor (9). This treatment concentrates the absorbed energy to intercellular electrolytes (8).…”
Section: Discussionmentioning
confidence: 99%
“…The modulated electro-hyperthermia (mEHT) system is a fast-developing complementary treatment method that is effective against different types of tumors (8,9). The principles involved are based on the classical method of hyperthermia, but the aim, besides the absolute increase in temperature, is to promote the direct absorption of electric-field energy by the extracellular fluid, thereby destroying the membrane of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5]. OTM method is well proven from the laboratory level to the clinical applications, [6]. It ignites the natural processes supporting the homeostasis of the system, re-establishing the communication harmony between the cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is a new type of heating: nanothermia. Using the above considerations, it concentrates on the nano-heating mechanism and the nano-manipulation of biomolecular changes [214,215]. It is supported by various experiments showing how energy absorption in the nano-range works.…”
mentioning
confidence: 99%